Implementasi Model Pembelajaran Aktif dalam Pendidikan Kewarganegaraan SD - Olga Griselda Tarigan; Hizkia Adventy Saragih; Chaterine Angelia Butar Butar; Jesica Elsadhay Purba; Devita Sari Purba; Jhon Daniel Anselino Malau (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the implementation of active learning models in Civic Education at the elementary school level. Active learning encourages student engagement, enhances conceptual understanding, and fosters critical thinking skills. This research employs a literature review approach by collecting data through observation, interviews, and document analysis in schools that apply active learning models. The findings indicate that methods such as group discussions, role-playing, and project-based learning significantly improve student motivation and civic awareness. Teachers also experience improvements in classroom management and designing interactive learning activities. However, challenges such as limited time, resources, and teacher training must be addressed for effective implementation. The study recommends curriculum adjustments and teacher training to optimize active learning models in Civic Education at the elementary level.